2018
DOI: 10.1137/17m1138479
|View full text |Cite
|
Sign up to set email alerts
|

On Symmetric But Not Cyclotomic Numerical Semigroups

Abstract: A numerical semigroup is called cyclotomic if its corresponding numerical semigroup polynomial P S pxq " p1´xq ř sPS x s is expressable as the product of cyclotomic polynomials. Ciolan, García-Sánchez, and Moree conjectured that for every embedding dimension at least 4, there exists some numerical semigroup which is symmetric but not cyclotomic. We affirm this conjecture by giving an infinite class of numerical semigroup families S n,t , which for every fixed t is symmetric but not cyclotomic when n ě max´8 pt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…In Section 6 we present an example of such an application. We show that 1 − x + x k − x 2k−1 + x 2k is not Kronecker for every k ≥ 4 (this was proven independently using a different method by Sawhney and Stoner [45]). This leads to the following result.…”
Section: Introductionmentioning
confidence: 76%
“…In Section 6 we present an example of such an application. We show that 1 − x + x k − x 2k−1 + x 2k is not Kronecker for every k ≥ 4 (this was proven independently using a different method by Sawhney and Stoner [45]). This leads to the following result.…”
Section: Introductionmentioning
confidence: 76%
“…Since, by assumption, we have e j = 0 for every gap j of S with 2 ≤ j < g, the series expansion of g−1 j=m(S) (1 − x j ) e j is of the form s∈S a s x s , and so in particular the coefficient of x g is zero. On comparing the coefficients of x g in both sides of (18), we obtain 0 = −e g , a contradiction. Proof.…”
Section: Cyclotomic Exponent Sequences Gaps and Minimal Generatorsmentioning
confidence: 88%
“…Therefore, every cyclotomic numerical semigroup is symmetric. The converse is generally not true; for instance, it can be shown that for every positive integer e ≥ 4, there exists a numerical semigroup of embedding dimension e that is symmetric but not cyclotomic [12,18]. Proposition 2.4 raises the question whether one can classify cyclotomic numerical semigroups for which P S decomposes into a small number of irreducible factors.…”
Section: Preliminariesmentioning
confidence: 99%
“…In fact, for any odd integer F with F ≥ 9, there is a numerical semigroup with Frobenius number F that is symmetric and non-cyclotomic. This was proven independently by García-Sánchez (in the appendix of [7]), Herrera-Poyatos and Moree [7] and Sawhney and Stoner [13]. In the latter two papers it is shown (by quite different methods) that, for every k ≥ 5, the polynomial…”
Section: Introductionmentioning
confidence: 87%
“…Consequently, n = pq or n = 2pq. From (13) and the equality P S (x) ≡ Φ n (x) (mod x 2 ), we obtain µ(n) = 1 and so n = pq and hence S = p, q . Theorem 3.2.…”
Section: Cyclotomic Numerical Semigroups Of Polynomial Lengthmentioning
confidence: 93%